2010
DOI: 10.1007/s13139-009-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Biological Gene Delivery Vehicles for Targeted Cancer Therapy: Beyond Viral Vectors

Abstract: Cancer persists as one of the most devastating diseases in the world. Problems including metastasis and tumor resistance to chemotherapy and radiotherapy have seriously limited the therapeutic effects of present clinical treatments. To overcome these limitations, cancer gene therapy has been developed over the last two decades for a broad spectrum of applications, from gene replacement and knockdown to vaccination, each with different requirements for gene delivery. So far, a number of genes and delivery vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
0
12
0
1
Order By: Relevance
“…The high level of autofluorescence and visible light absorption associated with in vivo imaging of fluorophores in the green spectrum greatly limits the tissue depth from which a clear fluorescent signal can be obtained. 54,55 However, the development of near-infrared (NIR) probes has allowed the in vivo analysis of fluorescence to become practical. 56 NIR probes reduce the level of background signal by increasing the signal-to-noise ratio and therefore facilitates fluorescent imaging at greater depths.…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%
“…The high level of autofluorescence and visible light absorption associated with in vivo imaging of fluorophores in the green spectrum greatly limits the tissue depth from which a clear fluorescent signal can be obtained. 54,55 However, the development of near-infrared (NIR) probes has allowed the in vivo analysis of fluorescence to become practical. 56 NIR probes reduce the level of background signal by increasing the signal-to-noise ratio and therefore facilitates fluorescent imaging at greater depths.…”
Section: Bioluminescence Imaging (Bli)mentioning
confidence: 99%
“…However, there are major limitations of the use of siRNA as a therapeutic tool, including its degradation by extracellular nucleases and poor cellular uptake. Although a number of vehicles, such as cationic liposomes, viral vectors and nanoparticles, have been used to transport siRNA, there are disadvantages of each method . Therefore, it remains a challenge to deliver interfering RNA to tumor cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Dual modification of lambda phage for targeted delivery of genes of interest to the immune system is a promising method for combating various diseases. The surface of the lambda phage displays specific ligands and the capsid encapsulates the selected gene sequence that is protected from degradation by enzymes[97]. Thoma et al[98] also confirmed that this strategy could produce higher immune response in the absence of any adjuvant and at physiological pH.…”
Section: Bacteriophages As Nanocarriersmentioning
confidence: 99%